Nanobodies in animal infectious disease control: diagnosis and therapy - Wang, Jing; Tong, Tiejin; Wu, Qiang (Frontiers in Cellular and Infection Microbiology, 2025)
Animal infectious diseases threaten livestock productivity, public health, and food security. Traditional monoclonal antibodies (mAbs) face limitations in diagnostics and therapy due to their large size, instability, and high cost. Nanobodies (Nbs), derived from camelid heavy-chain antibodies, offer superior properties—small size (~15 kDa), high stability, deep tissue penetration, and cost-effective production. Nbs feature extended CDR3 loops, enabling access to cryptic epitopes, and exhibit exceptional thermal/pH stability. They are generated by immunizing camelids, cloning VHH genes, and screening via phage/yeast display. High-throughput methods (ELISA, flow cytometry) allow rapid isolation of high-affinity Nbs. Compared to mAbs, Nbs are economically produced in prokaryotic systems and engineered into multivalent or Fc-fused formats for enhanced efficacy. In diagnostics, Nbs enable sensitive, low-cost detection of pathogens like PRRSV, ASFV, and avian influenza. Nb-based competitive ELISAs and lateral flow assays improve field surveillance. Therapeutically, Nbs neutralize pathogens by targeting viral proteins (e.g., blocking PRRSV-CD163 entry) or bacterial toxins (e.g., Staphylococcus enterotoxins). Nb-Fc fusions degrade ASFV proteins via TRIM-away, while intracellular Nbs disrupt Mycobacterium ESAT-6 or Toxoplasma actin dynamics. Challenges remain in Nb affinity optimization, intracellular delivery, and in vivo half-life. Solutions include fusion with cell-penetrating peptides or viral vectors (e.g., adenoviruses). Reducing cross-species immunogenicity and scaling production are critical for broader adoption. With advances in protein engineering, Nbs hold transformative potential for preventing, diagnosing, and treating animal diseases, offering scalable solutions for global health and food security.